The Effect of Service Quality, Facilities, Price Perception, and Trust on Service User Decisions - Jarwa Susila; Supawi Pawenang; Bambang Mursito (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of service quality, facilities, price perception, and trust on the decision to use auction services at the Surakarta State Assets and Auction Service Office (KPKNL). This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 40 respondents who are auction service users at KPKNL Surakarta. Data analysis techniques used include classical assumption tests, multiple linear regression analysis, model feasibility tests, and hypothesis tests using the SPSS program. The results of the study indicate that service quality, facilities, price perception, and trust simultaneously have a significant influence on the decision to use services. Partially, service quality has a positive and significant influence on the decision to use services, as do facilities and price perception. The trust variable has a positive and significant influence and is the most dominant variable in influencing the decision to use auction services. The coefficient of determination value indicates that most of the variation in the decision to use services can be explained by the independent variables in this study. This study is expected to be a consideration for KPKNL in improving service quality and become a reference for further research in the field of public services and government services.